2009
DOI: 10.1186/1479-5876-7-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of Modified Vaccinia Ankara (MVA) virus expressing 5T4 and high dose Interleukin-2 (IL-2) in patients with metastatic renal cell carcinoma

Abstract: Background: Interleukin-2 (IL-2) induces durable objective responses in a small cohort of patients with metastatic renal cell carcinoma (RCC) but the antigen(s) responsible for tumor rejection are not known. 5T4 is a non-secreted membrane glycoprotein expressed on clear cell and papillary RCCs. A modified vaccinia virus Ankara (MVA) encoding 5T4 was tested in combination with high-dose IL-2 to determine the safety, objective response rate and effect on humoral and cell-mediated immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 28 publications
0
52
0
Order By: Relevance
“…Results from phase I and II clinical studies of MVA-5T4 in renal, colorectal, and prostate cancer patients were encouraging and showed that immune responses were induced in almost all treated patients, and associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16). In particular, studies in RCC and colorectal cancer patients have detected an association between 5T4-specific (but not MVA) antibody responses and enhanced survival (9,12,16).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Results from phase I and II clinical studies of MVA-5T4 in renal, colorectal, and prostate cancer patients were encouraging and showed that immune responses were induced in almost all treated patients, and associations between 5T4-specific cellular or humoral responses and clinical benefit were reported in seven of nine studies (8)(9)(10)(11)(12)(13)(14)(15)(16). In particular, studies in RCC and colorectal cancer patients have detected an association between 5T4-specific (but not MVA) antibody responses and enhanced survival (9,12,16).…”
Section: Discussionmentioning
confidence: 88%
“…Previous data from phase II studies in RCC patients treated with MVA-5T4 and IL-2 also showed encouraging signs of clinical benefit (13,16). Currently, it is unclear why a survival advantage in patients with an intermediate prognosis treated with MVA-5T4 plus IL-2 was not seen.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on this understanding, current development of novel oncolytic vectors focuses not only on enhancing lytic replication, but also on harnessing the immune response, for example by the introduction of transgenes encoding cytokines [96,97], checkpoint inhibitors [98], ligands of T cell co-stimulatory receptors [99], bispecific T cell engagers [100][101][102] or tumor antigens [103][104][105], respectively, into the viral backbone. Combination therapies represent another approach to support immune responses to OV treatment, including additional application of cytokines [106], immune checkpoint inhibitors [107,108] or chemotherapeutics [109].…”
Section: Modes Of Action In Oncolytic Virotherapymentioning
confidence: 99%
“…In a high-dose study in which patients received MVA-5T4 injections at three-week intervals along with 600,000IU/kg interleukin 2 at weeks three, six, nine, and 12 (Kaufman, Taback, Sherman, et al, 2009). The results attributed a large number of adverse events to high-dose interleukin 2, but only two events (grade I fevers) to MVA-5T4, indicating that the regimen is safe and well tolerated in this population of patients.…”
Section: Viral Vector-based Immunotherapymentioning
confidence: 99%